2008
DOI: 10.1590/s0101-20612008000100005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da influência de amido e carragena nas características físico-químicas e sensoriais de presunto cozido de peru

Abstract: Amido e carragena são polissacarídeos utilizados na indústria de carne, possuem boas características sensoriais, boa afinidade e preservação da água no produto, além do amido ainda ter baixo custo.A legislação brasileira (BRASIL, 1998a) não permite a adição de amido em nenhum tipo de presunto, ao contrário de países como o Japão (KANBE et al., 1979) e os Estados Unidos (USA, 1999), cujos presuntos com alta qualidade apresentam este ingrediente em sua formulação.A legislação brasileira permite, por meio da Port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 5 publications
3
14
0
7
Order By: Relevance
“…Andrès et al (2006) when using agar hydrocolloids and xanthan gum, in chicken sausage obtained a reduction in hardness by increased concentrations of hydrocolloids in the formulations. Pedroso and Demiate (2008) found similar results by using carrageenan as a fat substitute in baked ham of turkey. Pietrasik (2003) found that samples of meat products, prepared with kappa-carrageenan had a substantial increase in hardness; in addition, the author states that carrageenan interacts with proteins to improve yield and texture of poultry meat products, especially when high water levels are used.…”
Section: Resultssupporting
confidence: 57%
“…Andrès et al (2006) when using agar hydrocolloids and xanthan gum, in chicken sausage obtained a reduction in hardness by increased concentrations of hydrocolloids in the formulations. Pedroso and Demiate (2008) found similar results by using carrageenan as a fat substitute in baked ham of turkey. Pietrasik (2003) found that samples of meat products, prepared with kappa-carrageenan had a substantial increase in hardness; in addition, the author states that carrageenan interacts with proteins to improve yield and texture of poultry meat products, especially when high water levels are used.…”
Section: Resultssupporting
confidence: 57%
“…Zhang and Barbut (2005) tested different starches (potato, cassava and modified starch) in a meat product made with chicken breast meat and also concluded that the use of modified starch reduced cooking loss. Pedroso and Demiate (2008) also reported that using starch and carragenan in turkey cooked ham resulted in lower values for cooking and reheating losses, indicating the desirable increase in the water-binding capacity due to the addition of hydrocolloids in this class of food.…”
Section: Resultsmentioning
confidence: 97%
“…In the Brazilian meat processing industry, the preferred starch is that which is extracted from cassava (Pedroso and Demiate 2008) due to a neutral flavor, availability, relatively low cost and a low gelatinization temperature that is compatible with the cooking temperatures of most meat products, such as sausages, mortadella and formed ham.…”
Section: Introductionmentioning
confidence: 99%
“…To compression force samples were prepared as 1.5 × 1.5 × 2.0 cm pieces and compressed at 66.67% of their height with a P36/R probe at a speed of 1.5 mm.s -1 (Pedroso & Demiate, 2008). …”
Section: Rheometrymentioning
confidence: 99%
“…The technological properties in this study aimed to evaluate the behavior of the samples during processing and their subsequent use in prepared foods, such as frozen and reheated foods for consumption (Pedroso & Demiate, 2008).…”
Section: Technological Propertiesmentioning
confidence: 99%